Reversal of Oral Anticoagulants for Intracerebral Hemorrhage Patients: Best Strategies - Fuh, Lanting; Sin, Jonathan H.; Goldstein, Joshua N.; Hayes, Bryan D. (Seminars in Respiratory and Critical Care Medicine, 2017)
In patients with acute intracerebral hemorrhage (ICH), one of the major concerns is ongoing bleeding or ICH expansion. Anticoagulated patients are at higher risk of ongoing expansion and worse outcome. It may be that rapid anticoagulation reversal can reduce the risk of expansion and improve clinical outcome. For those taking coumarins, the best available evidence suggests that intravenous vitamin K combined with four-factor prothrombin complex concentrate (4F-PCC) is the most rapid and effective regimen to restore hemostasis. For those on dabigatran, the highest quality data available for reversal are for idarucizumab, although it is not yet clear whether patients derive clinical benefit from this reversal. In the absence or failure of idarucizumab, activated prothrombin complex concentrate (aPCC) is recommended. For those on factor Xa inhibitors, the ideal reversal agent is not clear. Many providers use 4F-PCC or aPCC, but more specific agents are in clinical trials and may soon be available. In addition, the half-lives of the non–vitamin K antagonists are relatively short compared with warfarin, and so some patients may not have a clinically relevant coagulopathy at the time of presentation. Overall, the optimal reversal agent, when one is required, is a function of which anticoagulant the patient is taking.
Keywords: cerebral hemorrhage; anticoagulants; warfarin; dabigatran; rivaroxaban